Comparative effects of fractional radiofrequency and microneedling on the genitalia of postmenopausal women: Histological and clinical changes (Clinics, 2022)
Objectives: The authors aimed to evaluate clinical and histological changes induced by Fractional Radiofrequency (FRF) and microneedling in vulvar tissue.Methods: Thirty postmenopausal women were randomly divided into G1 (FRF) and G2 (microneedling) groups. Sub-ablative FRF was executed using disposable fractionated electrodes with an intensity of 8 mJ. Microneedling was performed using a derma roller system. The authors evaluated before and after treatment using the Vaginal Laxity Questionnaire (VLQ), EuroQol Five-Dimensional (EQ-5D) questionnaire, and the Blatt and Kupperman Menopausal Index (BKMI). Additionally, the authors performed biopsies of the labia majora for histological analysis pre- and post-treatment. Data were expressed as mean (± standard deviation). A paired t-test was used for intra-group comparison (pre- and post-treatment), with an independent t-test used to compare intergroup data (both pre- and post-treatment).Results: In the G1 group, the VLQ values showed differences compared to the pre-treatment values with the data obtained 60 days after the beginning of the sessions (p = 0.01). Similarly, the data changes of the G2 group proved to be significant (p = 0.001) across the same time interval. In comparing the groups, VLQ values were not different (p > 0.05). Regarding histological analysis, FRF demonstrated improvement concerning the number of fibroblasts, blood vessels, and fatty degeneration (p < 0.05) compared to the control. Additionally, FRF and microneedling samples showed higher type III collagen and vimentin expression in the immunohistochemical analysis (p < 0.05).Conclusions: The therapies were found to be effective in treating the flaccidity of the female external genitalia. Additionally, histological changes were observed after interventions suggesting collagen remodeling.